Pragmatic learning and study abroad: Effects of instruction and length of stay. (February 2015) - Alcón-Soler, Eva
Abstract: The study explores to what extent pragmatic instruction and length of study abroad (SA) influence learners ability to mitigate requests in e-mail communication. Sixty Spanish students, who were all enrolled for one academic year in six international language schools in the South of England, participated in the study. Whether participants were instructed on e-mail requests or not was the criteria used to create two groups: 30 in the experimental group, and 30 in the control group. Student initiated emails addressed to their teachers were collected at four different times, and analyzed with regard to the presence of lexical and syntactical request mitigators. In addition, learners' reports on the information learned since they arrived in England were used to observe the impact of instruction and length of SA on gains in the performance of request mitigators. A quantitative analysis of the data shows that instruction has an immediate effect on the production of e-mail request mitigators, but this effect is not sustained during the SA period, which may suggest that length of stay interacts with instruction. The qualitative analysis illustrates this interaction. It seems that knowledge gained from instruction is used and reconstructed through exposure to the target language to make informed decisions to choose when and how to use request mitigators according to the level of imposition of the e-mail request.